COMPARATIVE HEALING EFFICACY OF ACACIA PODS AND DERMAZINE CREAM ON BURN WOUNDS CREATED ON WISTAR ALBINO RAT - Ahmad, Mansur; Ladan, M. J.; Isah, S. A. (FUDMA JOURNAL OF SCIENCES, 2025)
Acacia nilotica has been widely recognized in traditional medicine for its wound healing and anti-inflammatory properties. This study aimed to evaluate the therapeutic efficacy of acacia nilotica administered topical, oral, and combined oral and topical routes in burn-induced albino rats. The Sumitra and Nidhi (2013) method was followed. Rats were given morphine I.P (0.02 mg/kg). Wounds were cleaned with saline and treated every three days with acacia 2% v/w oral, 2g/kg topical and combined 2% oral, 2g/kg topical. Treatment effects were compared with Dermazine, negative control (untreated burns), positive control (no injury). Changes in body weight, wound size over time, liver function tests (AST, ALT, ALP, TP, ALB, TB and DB), and malondialdehyde were assessed. Data were analyzed using one-way ANOVA with significance set at p < 0.05. The combination group (S+D) demonstrated significant improvement in wound contraction by Day 5 (3.10±1.10 mm²) as shown in table 1, increased body weight when compared the reference Dermazine (193.67±1.48 to 178.67±1.40a) and the negative control from day 0 to day 14 (187.33±1.38 to 160.66±2.02) respectively as shown in table 2, and restored liver enzyme levels compared to controls. Additionally, MDA levels were lowest in the S+D group (101.06±1.56 nmol/L), indicating reduced oxidative stress. All Acacia-treated groups showed better outcomes than Dermazine, with the S+D route showing the most notable effects. Acacia nilotica extract, especially when administered both orally and topically, significantly enhances burn wound healing, supports liver function recovery, and reduces oxidative stress. These findings validate traditional use of acacia and highlight...